UPAYA MEMINIMALKAN KESALAHAN PERILAKU INSTRUKSIONAL GURU DALAM PEMBELAJARAN BAHASA INGGRIS - Berlin Sibarani (BAHAS, 2008)
Teacher’s teaching behavior taking place during the real classroom teaching is determined by many interactive factors grouped into four categories, namely (1) linguistic knowledge about the nature of (a) language, (b) each language skills, and (b) each language aspect, (2) language teaching methods covering (a) their approaches, (b) procedures, (c) various techniques of them, (d) theories of language learning, and (e) knowledge of students’ characteristics and (3) the teacher’s reflection and meaning they made out of their teaching experiences. Lack of these knowledges may produce incorrect teaching behaviors which consequently cause low quality of students’ mastery of English. So the attempts to improve the students’ quality of English mastery should be begun by minimizing the incorrect teaching behaviors of English teachers and the incorrectness should be began by improving the teachers’ mastery of the three aspects. Key Words: behaviors, teaching and English.